Performing Child-Friendliness: A Dramaturgical and Intercultural Analysis of School Interactions in Indonesia - Fritz Hotman Syahmahita Damanik; Oman Sukmana; Tri Sulistyaningsih; Rachmad Kristiono Dwi Susilo; Tutik Sulistyowati; Sulismadi Sulismadi (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to examine how the concept of child-friendly schools is constructed, performed, and negotiated within Indonesian educational contexts by integrating perspectives from symbolic interactionism, dramaturgical theory, and intercultural communication. Employing a qualitative literature-based research design, the study systematically reviews and synthesizes scholarly articles, policy documents, and theoretical works published between 2015 and 2025, selected through a PRISMA-guided procedure to ensure methodological rigor, transparency, and relevance. The analysis reveals that child-friendliness in Indonesian schools operates not only as a formal policy discourse aligned with global child rights frameworks but also as a socially constructed and culturally mediated performance shaped by hierarchical relations, communal values, and high-context communication patterns. The findings highlight a persistent discrepancy between the “front-stage” representation of inclusive and non-violent school environments and the “back-stage” realities characterized by power asymmetries and limited student agency, indicating that compliance with policy standards does not necessarily translate into meaningful pedagogical transformation. The implications of this study suggest that fostering authentic child-friendly school environments requires context-sensitive, reflective, and participatory strategies that actively engage teachers, students, and communities, as well as a reorientation of educational policies toward deeper socio-cultural integration and transformative practice.